Obtaining Cellulose-Available Raw Materials by Pretreatment of Common Agro-Forestry Residues With Pleurotus spp. - Galić, Milica; Stajić, Mirjana; Vukojević, Jelena; Ćilerdžić, Jasmina (Frontiers in Bioengineering and Biotechnology, 2021)
The goals of the present study were to characterize the profile of ligninolytic enzymes in five Pleurotus species and determine their ability to delignify eight common agro-forestry residues. Generally, corn stalks were the optimal inducer of Mn-dependent peroxidase activity, but the activity peak was noted after wheat straw fermentation by P. eryngii (3066.92 U/L). P. florida was the best producer of versatile peroxidase, especially on wheat straw (3028.41 U/L), while apple sawdust induced the highest level of laccase activity in P. ostreatus (49601.82 U/L). Efficiency of the studied enzymes was expressed in terms of substrate dry matter loss, which was more substrate- than species-dependent. Reduction of substrate dry mass ranged between 24.83% in wheat straw and 8.83% in plum sawdust as a result of fermentation with P. florida and P. pulmonarius, respectively. The extent of delignification of the studied substrates was different, ranging from 51.97% after wheat straw fermentation by P. pulmonarius to 4.18% in grapevine sawdust fermented by P. ostreatus. P. pulmonarius was also characterized by a the highest cellulose enrichmentselectivity index (3.846.54), ) and P. ostreatus by very low one (1.55). which was slightly lower than that obtained for P. salignus (5.27). The tested biomass is a highly abundant but underutilized source of numerous value-added products, and a cocktail of ligninolytic enzymes of Pleurotus spp. could be useful for its environmentally and economically friendly transformation.